Factors Influencing Health Care Providers Payment Reforms in Central and Eastern European Countries - Costase Ndayishimiye; Marzena Tambor; Daiga Behmane; Antoniya Dimova; Alina Dūdele; Aleksandar Džakula; Barbora Erasti; Péter Gaál; Triin Habicht; Pavel Hroboň; Liubove Murauskienė; Tamás Palicz; et al. (SAGE Publishing, 2024)
Central and Eastern European (CEE) countries have recently implemented reforms to health care provider payment systems, which include changing payment methods and related systems such as contracting, management information systems, and accountability mechanisms. This study examines factors influencing provider payment reforms implemented since 2010 in Bulgaria, Croatia, Czechia, Estonia, Latvia, Lithuania, Hungary, Poland, and Romania. A four-stage mixed methods approach was used: developing a theoretical framework and data collection form using existing literature, mapping payment reforms, consulting with national health policy experts, and conducting a comparative analysis. Qualitative analysis included inductive thematic analysis and deductive approaches based on an existing health policy model, distinguishing context, content, process, and actors. We analyzed 27 payment reforms that focus mainly on hospitals and primary health care. We identified 14 major factor themes influencing those reforms. These factors primarily related to the policy process (pilot study, coordination of implementation systems, availability of funds, IT systems, training for providers, reform management) and content (availability of performance indicators, use of clinical guidelines, favorability of the payment system for providers, tariff valuation). Two factors concerned the reform context (political willingness or support, regulatory framework, and bureaucracy) and two were in the actors' dimension (engagement of stakeholders, capacity of stakeholders). This study highlights that the content and manner of implementation (process) of a reform are crucial. Stakeholder involvement and their capacities could influence every dimension of the reform cycle. The nine countries analyzed share similarities in barriers and facilitators, suggesting the potential for cross-country learning.